HUBUNGAN MOTIVASI EKSTRINSIK DENGAN PRESTASI BELAJAR SISWA KELAS V SD SE-GUGUS I KECAMATAN TUALANG PERAWANG - Rika Islamiati; Eddy Noviana; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Extrinsic motivation has a very important role decisive and encouraging students to learn with full attention and concentration in a lesson, so that the attainment of the objectives expected by the students that good learning performance with increased learning achievement. This study aims to determine the relationship between the extrinsic motivation of students with student achievement class V SD cluster I Tualang district Perawang. This research method was correlational. The sampling technique using one of the techniques in simple random sampling. Methods of data collection using questionnaires and engineering documentation of the average value of first semester report card of the school year 2015/2016. The analysis technique used is the technique of analysis Product Moment. Test requirements analysis in the form of normality test and linearity test. Engineering analysis and test requirements analysis using SPSS 20. The results showed that there is a positive relationship between extrinsic motivation and academic achievement of students in class V SD cluster I Tualang district Perawang, obtained rxy of 0.511 with a degree of correlation being as well as extrinsic motivation to contribute to the achievement learning by 26.1%. The results of hypothesis testing using correlation, there is a significant relationship between extrinsic motivation and academic achievement of students in class V SD cluster I Tualang district Perawang, obtained rhitung (5,885)> r table (1.984), then Ho is rejected and means Ha acceptable means there significant relationship between extrinsic motivation and academic achievement grade elementary school students throughout cluster I the District Tualang Perawang.Key Word: The extrinsic motivation, learning achievement